Analisis Kinerja Karyawan Berdasarkan Pelatihan Kerja dan Disiplin Kerja Pada PD. Bakso Momo Jaya Tasikmalaya - Asep Jono; Kusuma Agdhi Rahwana; Arga Sutrisna (Journal of Indonesian Management, 2022)
This study aims to determine Employee Performance Analysis Based on Job Training and Work Discipline In PD. Bakso Momo Jaya. The method used is quantitative with a sample of 50 respondents from employee PD. Bakso Momo Jaya. The data used is primary data. The analytical tool used in this study is multiple linear regression using SPSS version 25. The results of the study show that the job training felt by employee PD. Bakso Momo Jaya have very good criteria. Work discipline on employee PD. Bakso Momo Jaya has very good criteria. Simultaneously, job training and work discipline have a significant influence on employee performance. Partially job training has a significant effect on employee performance. Partially, work discipline has a significant effect on employee performance.